Differential Ly-6C expression identifies the recruited macrophage phenotype, which orchestrates the regression of murine liver fibrosis - Ramachandran, Prakash; Pellicoro, Antonella; Vernon, Madeleine A; Boulter, Luke; Aucott, Rebecca L; Ali, Aysha; Hartland, Stephen N; Snowdon, Victoria K; Cappon, Andrea; Gordon-Walker, Timothy T; Williams, Mike J; Dunbar, Donald R; et al. (Proceedings of the National Academy of Sciences - PNAS, 2012)
Although macrophages are widely recognized to have a profibrotic role in inflammation, we have used a highly tractable CCl(4)-induced model of reversible hepatic fibrosis to identify and characterize the macrophage phenotype responsible for tissue remodeling: the hitherto elusive restorative macrophage. This CD11B(hi) F4/80(int) Ly-6C(lo) macrophage subset was most abundant in livers during maximal fibrosis resolution and represented the principle matrix metalloproteinase (MMP) -expressing subset. Depletion of this population in CD11B promoter-diphtheria toxin receptor (CD11B-DTR) transgenic mice caused a failure of scar remodeling. Adoptive transfer and in situ labeling experiments showed that these restorative macrophages derive from recruited Ly-6C(hi) monocytes, a common origin with profibrotic Ly-6C(hi) macrophages, indicative of a phenotypic switch in vivo conferring proresolution properties. Microarray profiling of the Ly-6C(lo) subset, compared with Ly-6C(hi) macrophages, showed a phenotype outside the M1/M2 classification, with increased expression of MMPs, growth factors, and phagocytosis-related genes, including Mmp9, Mmp12, insulin-like growth factor 1 (Igf1), and Glycoprotein (transmembrane) nmb (Gpnmb). Confocal microscopy confirmed the postphagocytic nature of restorative macrophages. Furthermore, the restorative macrophage phenotype was recapitulated in vitro by the phagocytosis of cellular debris with associated activation of the ERK signaling cascade. Critically, induced phagocytic behavior in vivo, through administration of liposomes, increased restorative macrophage number and accelerated fibrosis resolution, offering a therapeutic strategy to this orphan pathological process.